Influence of subjects’ characteristics and cognitive factors on the perception of the odors from aromatic plants and physiological response - Pei, Shichun; Qu, Yueying; Lu, Jing; Yao, Lei; Zhang, Nan (Building and environment, 2025)
•Gender and anxiety affect the perception of odor familiarity and pleasantness.•People with anxiety or knowing odor sources react faster to arousal and familiarity.•Gender and anxiety show effects on heart rate and galvanic skin response to odors.•Knowing odor sources shows greater impacts on the prefrontal and occipital EEG.•Women's θ waves in the prefrontal lobe decrease more when smelling plant odors. Odors with natural attributes could construct spatial olfactory environments for aesthetic and health benefits and affect the perception of the overall environment. The study on the influence of the subjects’ characteristics and cognitive factors on their perception of plants’ odors and accompanying physiological responses is still limited. To investigate how gender, anxiety, fragrance usage habits, and odor information awareness affect the perception of plant odors, thirteen aromatic plants were chosen as odor stimuli, and both subjective perception and physiological responses were evaluated. The results indicated that the above four characteristics and cognitive factors affected the perception and physiological responses in different ways. Men's familiarity scores for odors were generally higher than those of women, while anxiety state affected odor preference. Anxious individuals and those who knew the odor source reacted faster when evaluating odor arousal and familiarity. Anxiety state had a greater impact on galvanic skin response (GSR). The GSR changes of anxious people were generally lower than those of non-anxious people. The effect of the anxiety state on the electroencephalogram (EEG) response varied depending on the type of odor. Gender also affected EEG responses. Women's prefrontal lobes were more activated by plant odors. Odor information had a greater impact on EEG than other factors. Knowing the odor source led to a more significant decrease in θ waves in multiple brain regions. These results provide a reference for the subjective perception differences of plant odors and their potential physiological response mechanisms among subjects with different characteristics and odor cognition.